Estimating Physical Interactions with Neighboring Student for Detecting Active Learners in the Computer Classroom (International Conference on Computers in Education, 2023)
In the classroom, some students may isolate themselves, hesitant to seek help due to psychological barriers. These students need active addressing from Teaching Assistants (TAs). Especially in computer classroom due to the types of study. However, there are cases where some classes are arranged with only a few TAs for a large number of students, and it may cause that students who should be approached may be overlooked. In order to support isolated learners, this study estimates the physical interaction with neighboring student based on the learner video in a computer classroom. Analysis of learner video reveals the possibility of using a depth camera to separate movements and estimating interactions. This result can be applied to the TA support system which detects isolated learners.